Regional Head Role in Effective Development: Qualitative Study in Nabire, Central Papua - Jean Marzel Ngantung; Yerri Lukas Tabuni (Jurnal Studi Pemerintahan dan Akuntabilitas, 2026)
Purpose: This study examines the role of regional heads in improving development effectiveness in Nabire District, Nabire Regency, Central Papua Province. It analyzes the gap between formal leadership authority and real development outcomes during the region’s transition into the new provincial structure. Research methodology: A descriptive qualitative approach was used with purposeful and snowball sampling. Data were collected from 60 informants—including coastal and highland indigenous Papuans, migrants, and religious leaders—through interviews, observation, and documentation. Analysis followed Miles and Huberman’s interactive model. Results: The findings show that regional heads significantly shape development effectiveness through strategic infrastructure interventions that strengthen socio-economic conditions. Improvements in the Human Development Index (HDI) during the 2021–2026 leadership period include increases in life expectancy, expected years of schooling, and mean years of schooling. These outcomes were driven by decisive leadership, strong agency coordination, and community participation. Key achievements include Kalibobo Market revitalization, road rehabilitation, and enhanced urban planning. Conclusions: Proactive and innovative leadership, supported by strong political will, is crucial for realizing the “Safe, Independent, and Prosperous Nabire” vision. However, challenges remain in economic performance, data accuracy, and sustainability of community empowerment programs. Limitation: The single-district scope limits broader generalization, the short observation period restricts long-term assessment, and statistical discrepancies require careful interpretation. Contribution: This study provides empirical evidence linking leadership roles to HDI improvement, highlights the impact of leadership transition, and offers practical insights for governance in the new Central Papua Province.